Evaluation of Printability of PVA-Based Tablets from Powder and Assessment of Critical Rheological Parameters - Jonas Lenhart; Florian Pöstges; Karl G. Wagner; Dominique J. Lunter (MDPI AG, 2024)
Fused deposition modeling (FDM) is a rather new technology in the production of personalized dosage forms. The melting and printing of polymer-active pharmaceutical ingredient (API)-mixtures can be used to produce oral dosage forms with different dosage as well as release behavior. This process is utilized to increase the bioavailability of pharmaceutically relevant active ingredients that are poorly soluble in physiological medium by transforming them into solid amorphous dispersions (ASD). The release from such ASDs is expected to be faster and higher compared to the raw materials and thus enhance bioavailability. Printing directly from powder while forming ASDs from loperamide in Polyvinylalcohol was realized. Different techniques such as a change in infill and the incorporation of sorbitol as a plastisizer to change release patterns as well as a non-destructive way for the determination of API distribution were shown. By measuring the melt viscosities of the mixtures printed, a rheological model for the printer used is proposed.